Student-athletes` mental health in the european sport school context: A scoping review - Saarinen, M.; Mcdougall, M.; Gjesdal, S.; Bjørndal, C. T. (Journal of Clinical Sport Psychology, 2026)
The purpose of this scoping review was to provide an overview of literature exploring adolescent student-athlete mental health in the European sport school context, with particular emphasis on gender. Five databases were searched for relevant literature: PsycINFO, SPORTDiscus, Scopus, PubMed, and Google Scholar. In total, 26 peer-reviewed published articles met the inclusion criteria. The review indicated that literature on adolescent student-athlete mental health in Europe is dominated by a preoccupation with mental illness rather than mental health and the use of quantitative and cross-sectional research designs. Many studies reported that student-athletes demonstrated lower prevalence and incidence rates of mental illness symptoms compared to the general youth population. Female student-athletes consistently demonstrated higher prevalence of mental illness symptoms compared to males. Practitioners working with adolescent student-athletes can improve their mental health literacy to understand mental health beyond the confines of mental illness and target key areas of burnout and the female experience of mental health.